Conservation and Development: Implementation of The Storyline at The National Awakening Museum, Stovia Building-Jakarta - Ika Yuni Purnama (Badan Penerbit STIEPARI Press, 2023)
Balancing conservation and museum development is one of the biggest challenges in managing historic spaces. In 2012, the Stovia Jakarta Building became a museum of the history of medicine and the struggle of Indonesian youth. Based on storyline analysis, this paper explores the implementation of historical storylines for the collection of relics at the Stovia medical school building in Jakarta describes the development of medical science in the past regarding the history of the struggle of Indonesian youth and tourism, and heritage management. This observation is then examined in the plot of the story, the description of the socio-political situation, and the changes in the Dutch East Indies during the transitional period of the 19-20th centuries which gave birth to a revival and a national movement. This paper explores whether historical storylines are part of spatial development and reflect new understandings of spatial planning. Storyline processing supports conservation reconciliation and regenerates the development of interior spaces. The analysis shows that while some of the storyline principles have been well implemented, they have not been supported by information technology for the benefit of tourism development, and the needs of visitors